Profiling of fatty acids and rumen ecosystem of sheep fed on a palm kernel cake-based diet substituted with corn - Saeed, Osama A.; Sani, Umar M.; Sazili, Awis Q.; Akit, Henny; Alimon, Abdul R.; Samsudin, Anjas A. (MDPI, 2023)
The purpose of this study was to analyze the effects of corn substitution on the rumen functions and fatty acid profile of Dorper lambs fed a diet based on palm kernel cake (PKC). Corn was replaced with PKC basal diet at the following levels: C0% = (0% corn + 75.3% PKC), C1% = (5% corn + 70.3% PKC) and C2% = (10% corn + 65.3% PKC) of diet. The rumen fermentation was carried out in vitro, and feeding trials were in vivo. Twenty-seven lambs were used to determine gastrointestinal tract content and rumen fluid fatty acid. Rumen liquor was obtained from four fistulae Dorper sheep and incubated with 200 mg of each treatment for 24 and 72 h. In vitro organic matter digestibility (IVOMD), in vitro dry matter digestibility (IVDMD), volatile fatty acids (VFA), methane estimation (CH4 ), rumen microbial population and fatty acid biohydrogenation were determined. The results of the in vitro study showed there were no significant differences in IVDMD, IVOMD, NH3 -N, pH and VFA at 72 h. Higher significant CH4 production was observed in C0% when compared with C1% and C2%. Microbial population did not differ significantly between treatment groups. The rates of biohydrogenation were not affected by corn substitution, although a significant difference was observed in C18:1n9 (in vitro) and C18:1 t-11 (in vivo). In conclusion, the present study indicated that the corn substitution in the PKC diets maintained fermentation characteristics with an increase in unsaturated fatty acids in the rumen.